2010
DOI: 10.1002/marc.201000154
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine as a Nucleophile and Antioxidant for Fast Aminolysis of RAFT Polymers in Air

Abstract: The bifunctional role of hydrazine as a potent nucleophile and antioxidant was investigated for the rapid aminolysis of RAFT polymers within minutes in air with effective suppression of the formation of disulfides. Using both dithioesters and trithiocarbonates as model compounds, we showed that hydrazine exhibited a significantly improved aminolysis rate when compared with a commonly used primary alkyl amine. On the basis of the exellent results with CTAs, we further studied the aminolysis of RAFT polymers pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 42 publications
0
77
0
Order By: Relevance
“…[34] It has been reported that the use of hydrazine as nucleophile is advantageous both in giving a very rapid reaction and little disulfide formation even when the process was carried out in air. [375] However, Lee et al [176] found disulfide formation to be significant during the hydrazinolysis of St/AcS copolymers. DADMAC [113,440] N Cl Ϫ 427 [589] O OC(CH 3 ) 3 OC(CH 3 ) 3 O O 428 [590] O O O O 429 [590] O O O O n 430 [591] O O…”
Section: Radical-induced Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…[34] It has been reported that the use of hydrazine as nucleophile is advantageous both in giving a very rapid reaction and little disulfide formation even when the process was carried out in air. [375] However, Lee et al [176] found disulfide formation to be significant during the hydrazinolysis of St/AcS copolymers. DADMAC [113,440] N Cl Ϫ 427 [589] O OC(CH 3 ) 3 OC(CH 3 ) 3 O O 428 [590] O O O O 429 [590] O O O O n 430 [591] O O…”
Section: Radical-induced Oxidationmentioning
confidence: 99%
“…[44] The first reports involved the use of N,N-dialkyl dithiocarbamate derivatives as ATRP initiators. Dithiocarbamates do not provide effective control over the polymerization [241] MMA, St 456 Propylamine Network cleavage [603] BA, St 441 Butylamine/TCEP/BA In situ thiol-ene multiblock cleavage [604] PEGA 47 Butylamine/TCEP/divinyl sulfone In situ thiol-ene [281] MA, DMAm, NIPAm, St, C 2 H 5 S (121) Hydrazine - [375] St, PEGMA Ph (54, 18) Hydrazine - [375] St Ph (18) Hydrazine Used in thiol-epoxide [193] St Ph (18) DEAm (18) Hydrazine In situ thiol-epoxide [193] St/AcS Ph (11) Hydrazine Au nanoparticles [176] EGDMA, 421, 420 Ph (18) Hexylamine Used in thiol-ene or other reaction [588] St PhCH 2 S 1) KOH, 2) Zn/AcOH Au nanoparticles [338] St PhCH 2 S (89) Ethylene diamine Initiator for ROP C [339] HPMAm Ph (11) NaBH 4 /PBu 3 In situ thiol-ene (AA) [161] HPMAm Ph (68) Butylamine MeOH/degassed used in thiol-ene [307] NIPAm Ph (18) NaBH 4 Used in thiol-ene [247] MMA Ph (18) Hexylamine In situ thiol-ene [220] HPMAm Ph (18) Hexylamine In situ thiol-ene [220] NIPAm CH 2 (CO 2 H)CH 2 S (179) Hexylamine In situ thiol-ene [220] NIPAm C 4 H 9 S (159) Hexylamine/DMPP Used in thiol-ene [446] NIPAm C 12 H 25 S (123) Hexylamine/Bu 3 Ph Used in thiol-ene [398] Am Ph (18) NaBH 4 Used in thiol ene [244] DEAm Ph ( StMe OEt Ozone --(C¼O)SOEt [606] BA OEt Ozone --(C¼O)SOEt [607] iBoA 2-pyridyl Air AIBN, THF/Ph 3 P -OH [605] MMA, acrylates Ph Air AIBN, THF/Ph 3 P -OH [182,605] St, acrylates P n S Air AIBN, THF/Ph 3 P -OH [182] MA, BA CH 2 Ph Air AIBN, THF/Ph 3 P -OH [182] St CH 2 Ph Air AIBN, THF/Ph 3 P -OH …”
Section: Atrp-raftmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such end-groups are easily converted under a range of conditions including aminolysis, [107,108] hydrazinolysis, [109] and hydride [110] cleavage with aminolysis being the preferred route. [105] Reactions can be conducted such that the macromolecular thiol is generated in situ and used in a subsequent reaction in a one-pot process, the thiol may be trapped or in some instances the macromolecular species can be isolated and characterized prior to use in a subsequent step.…”
Section: Raft and Thiol-based Reactionsmentioning
confidence: 99%
“…Under UV-irradiation of appropriate wavelength, the cross-linking reaction of the outer region is carried out. Finally, the RAFT-core is decomposed via aminolysis [28] to achieve hollow sphered particles. The success of the procedure is monitored by size exclusion chromatography (SEC)-measurements of the material after the different steps of synthesis as well as by dynamic light scattering (DLS).…”
Section: Introductionmentioning
confidence: 99%